Ultra–Precision Turning of Electroless–Nickel: Effects of crystal orientation and origin of diamond tools - Pramanik, Alokesh; Soon, Neo; Rahman, Mustafizure; Li, X; Sawa, M; Meada, Y (Springer U K, 2009)
This paper deals with (i) the performance of natural and artificial diamond tools and (ii) the effects of crystal orientations at rake face of diamond tool for long distance (>200 km) ultraprecision machining of electroless nickel. The criteria for cutting performance of the diamond tool include flank wear, crater wear, workpiece surface finish, and cutting forces. Experimental results show that the natural diamond tool has superior performance compared to the artificial one as it experienced lower cutting forces and lower flank and crater wears. It was also found that the cutting tool with {110} crystal orientation at rake face performs better than the tool with {100} crystal orientation in terms of amount of wear, surface finish, and cutting forces.